So far away from me: Firm location and the managerial ownership effect on firm value - Benson, Bradley W.; Chen, Yu; James, Hui L.; Park, Jung Chul (Journal of Corporate Finance, 2020)
We examine the relation between CEO delta, firm locality, and firm value for a sample of 7749 firm-year observations. We find that CEO delta is more value-enhancing for rural firms, those associated with exacerbated agency conflicts resulting from decreased observability of managerial investment decisions and higher levels of information asymmetry. Further, the positive relation between CEO delta and firm value is stronger for rural firms with higher levels of information asymmetry or in less religious areas. Our findings imply that managerial ownership is more effective in mitigating agency conflicts in rural areas with higher levels of information asymmetry and lower degrees of local trustworthy constituents. Our results are robust to alternative definitions of urban/rural firms, the inclusion of additional control variables, and various tests controlling the endogeneity between firm location and value. Finally, the results do not appear to be driven by reverse causality.